Phase behavior, diffusion, structural characteristics, and pH of aqueous hydrophobic ionic liquid confined media: insights into microviscosity and microporsity in the [C(4)C(4)im][NTf2] + water system - Nanda, Raju; Kumar, Anil (Journal of Physical Chemistry B, 2015)
We present our studies on the physicochemical properties of water confined in Dibutylimidazolium bis(trifluoromethanesulfonylimide) ([C(4)C(4)im][NTf2]) reverse micelles through the NMR relaxation measurements that provide us an understanding of microviscosity and pH in the confined condition. We present experimental results on phase behavior, diffusion, structural characteristics and pH in aqueous ionic liquid-confined media. The ternary phase diagram was constructed by the cloud point measurements and the microheterogeneous regions were detected by the measurement of bulk viscosity and diffusion coefficients of K-4[Fe(CN)(6)] inside the homogeneous microemulsion systems through the cyclic voltammetric (CV) measurements. The size of the microemulsion systems was characterized by the dynamic light scattering (DLS) method. The H-1 NMR spectra of homogeneous microemulsion systems were taken which indicates the presence of bound and free water molecules inside the microemulsion system. The NMR spinlattice relaxation time (T-1) of water molecules in its homogeneous microemulsion systems were measured and the reorientational correlation time (t(c)) of water molecules obtained from it indicates that the fluidity of homogeneous confined media decreases with the decrease in the composition of water. Microviscosity of the aqueous confined media was calculated from the measured T-1 relaxation time values by applying the DebyeStokes equation and correlated with the bulk viscosity of the samples. It was observed that both the microviscosity and bulk viscosity show inverse relationship. The fraction of bound and free water molecules were calculated from the measured T-1 values. NMR spinspin relaxation time (T-2) of water molecules in its homogeneous microemulsion systems were measured with the varying pH of the aqueous core. A change in the T-2 relaxation time of the water proton was observed proposing an exchange of proton between the H2O and -OH group of the TX-100 molecules. Finally, methyl orange (MO) was used as a UVvis spectrophotometric molecular probe and the measured lambda(max) values of the probe were used for the detection of micropolarity of the homogeneous aqueous confined media and was found to be increase with the increase in the size of the confined media.